PENGARUH MODEL PEMBELAJARAN SENTRA BAHAN ALAM TERHADAP KEMAMPUAN SAINS DAN BERBICARA ANAK KELOMPOK B DI TAMAN KANAK-KANAK - PRATIWI, AJENG PUTRI; RIVAI, RIKA KURNIA; -, NOPIANA (Jurnal Pendidikan Usia Dini, 2017)
This research aimed to examine (1) the effect of natural centered model of learning method for group B children scientific skills (2) the effect of natural centered model of learning method for group B children speaking skills (3) the effect of natural centered model of learning method for group B children scientific and speaking skills.This research uses a quantitative approach which is using Nonequivalent Control Group Design. The reserchwas conducted in group B at TK PGRI 3 Pandaanand TK PKK V Pandaan.Experimental groups totaling 44 children and40 children for controlling groups. The research data are collected using observation method, documentation and observation guide used to collect data about scientific and speaking skills. Analysis data is using ANOVA and MANOVA statistic test with SPSS 21.0. This research results show that (1) Natural centered model of learning method is effecting group B children scientific skills,it is evident from the ANOVA test results demonstrate the value of Fcount is 163,661 with sig. 0,000 smaller than 0.05. (2) Natural centered model of learning method is effecting group B children speaking skillsit is evident from the ANOVA test results demonstrate the value of Fcount is 61,992 with sig. 0,000 smaller than 0.05.(3) Natural centered model of learning method is effecting group B children scientific and speaking skills, it is evident from the ANOVA test results demonstrate the value of Fcount or wilks’lambada is 163,661 with sig. 0,000 smaller than 0.05. Because the third hypothesis states <0.05 then declared acceptable.According this research result, it can be concluded as (1) Natural centered model of learning method is effecting scientific skills(2) Natural centered model of learning method is effecting speaking skills (3) Natural centered model of learning method is effecting scientific and speaking skills. It will be advised to early childhood education institutes to apply Natural centered model of learning method as one of learning model which stimulate scientific and speaking skills on group B kindergarten children. Natural centered model of learning method is effecting group B children scientific skills. Keywords: Natural centered, scientific and speaking